Integrating Islamic Values into HR Practices to Combat Fraud in Islamic Finance - Wilchan Robain; Abdul Rahman (Yayasan Darussalam Bengkulu, 2026)
The rapid growth of Islamic financial institutions has highlighted the need for HR practices that integrate Islamic values, particularly in preventing fraud. This study investigates the relationships between recruitment, selection, trustworthy human resources (HR), and fraud-free systems within Islamic financial institutions. Using Structural Equation Modeling (SEM) with SmartPLS 4, the study tests the direct and indirect effects of recruitment and selection on fraud prevention through trustworthy HR. The results show that both recruitment and selection significantly influence the formation of trustworthy HR, which in turn reduces the risk of fraud. The study also finds that trustworthy HR mediates the relationship between recruitment, selection, and fraud prevention. The research highlights the importance of aligning recruitment and selection strategies with Islamic ethical principles to ensure the development of a trustworthy workforce. The findings contribute to the literature on Islamic HRM by offering a model that links HR practices to fraud prevention. This study suggests that HR managers in Islamic financial institutions should prioritize value-based recruitment and selection processes, along with ongoing ethical training, to foster a culture of integrity and transparency. Future research could examine the role of other organizational factors, such as leadership and external regulations, in preventing fraud.